1980
DOI: 10.1007/bf02414736
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation, loss and molecular distribution of cadmium inMytilus edulis

Abstract: In Mytilus edulis, accumulation and loss of Cd were analyzed under experimental conditions. Cd uptake by the whole soft body is linear, increasing significantly with increasing Cd concentrations in the uptake medium. Until 100 #g Cd 1-1, neither limitation of uptake nor any saturation process can be observed. Loss of Cd, measured after transfer of experimentally contaminated mussels to natural sea water, is exponential; biological half lives vary between 14 and 29 days. Gills are the primary sites of Cd uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

1980
1980
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 18 publications
6
20
0
Order By: Relevance
“…Soon after the Noel-Lambot report, Talbot and Magee (2) demonstrated that similar proteins were present in mussels exposed to contaminating metals in the natural environment. More recent studies have verified the presence of BPs in Mytilus edulis following exposure to cadmium (3)(4)(5) and mercury (6). In a related species, Mytilus galloprovincialis, BPs have also been demonstrated following exposure to both cadmium (7) and copper (8)(9)(10).…”
Section: Introductionmentioning
confidence: 91%
“…Soon after the Noel-Lambot report, Talbot and Magee (2) demonstrated that similar proteins were present in mussels exposed to contaminating metals in the natural environment. More recent studies have verified the presence of BPs in Mytilus edulis following exposure to cadmium (3)(4)(5) and mercury (6). In a related species, Mytilus galloprovincialis, BPs have also been demonstrated following exposure to both cadmium (7) and copper (8)(9)(10).…”
Section: Introductionmentioning
confidence: 91%
“…In addition, the difference in half times of vertebrates and invertebrates raises the question whether there are fundamental differences in the mechanism of heavy-metal detoxication in both systematic groups. This point is dealt with in detail by Scholz (1979Scholz ( , 1980. Scholz (1980) SOME METABOLIC RESPONSES I should like to add a few remarks on some recently observed influences of sublethal Cd contamination on metabolic processes of adult invertebrates.…”
Section: Aspects Of Accumulation and Eliminationmentioning
confidence: 98%
“…This point is dealt with in detail by Scholz (1979Scholz ( , 1980. Scholz (1980) SOME METABOLIC RESPONSES I should like to add a few remarks on some recently observed influences of sublethal Cd contamination on metabolic processes of adult invertebrates. In decapod crustaceans it has been observed that Cd uptake rate decreases in the order: Eupagurus bernhardus > Carcinus maenas > Hriocheir sinensis.…”
Section: Aspects Of Accumulation and Eliminationmentioning
confidence: 98%
See 2 more Smart Citations